1992
DOI: 10.1148/radiology.184.3.1509054
|View full text |Cite
|
Sign up to set email alerts
|

Hepatosplenic schistosomiasis: comparison of sonographic findings in Brazilian and Sudanese patients--correlation of sonographic findings with clinical symptoms.

Abstract: Twenty-seven Brazilian and 32 Sudanese patients with hepatosplenic schistosomiasis from areas where the disease is endemic were examined with ultrasound (US). Hyperechoic periportal areas indicating periportal fibrosis (PPF) were present in all patients irrespective of their origin. Nonspecific findings were splenomegaly (all patients), gallbladder wall thickening (81% and 92%, respectively, in Brazilian and Sudanese patients), portal vein (74% and 87%, respectively) and splenic vein (59% and 70%, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…endoscopic and sonographic findings and variceal bleeding were compared had conflicting results: whereas in earlier studies a relationship between the sonographic grade of periportal fibrosis, the occurrence of variceal haemorrhage prior to examination and/or the grade of oesophageal varices had not been found (Homeida et al 1988;Davidson et al 1991), more recent investigations showed that the sonographic grade of periportal fibrosis is related to prior variceal haemorrhage (Richter et al 1992a;Domingues et al 1993;Abdel-Wahab et al 1993;Eltoum et al 1994;Gerspacher-Lara et al 1997).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…endoscopic and sonographic findings and variceal bleeding were compared had conflicting results: whereas in earlier studies a relationship between the sonographic grade of periportal fibrosis, the occurrence of variceal haemorrhage prior to examination and/or the grade of oesophageal varices had not been found (Homeida et al 1988;Davidson et al 1991), more recent investigations showed that the sonographic grade of periportal fibrosis is related to prior variceal haemorrhage (Richter et al 1992a;Domingues et al 1993;Abdel-Wahab et al 1993;Eltoum et al 1994;Gerspacher-Lara et al 1997).…”
Section: Discussionmentioning
confidence: 98%
“…For the latter classification, DoehringSchwerdtfeger et al (1992) have shown that whereas interobserver variance may influence the grading of incipient fibrosis, this is unlikely to happen in the more advanced stages, where variceal bleeding occurs. At a recent meeting in Niamey it has been recognized that the reproducibility of the grading of fibrosis whichever classification had been applied so far, may be limited by several subjective and objective factors (Homeida et al 1988;Doehring-Schwerdtfeger et al 1989;Richter et al 1992a. This applies particularly to the 'Cairo' methodology and a similar methodology used by AbdelWahab et al (1993) which are based on the measurement of the external diameter of portal branches because it is not clearly defined where to measure.…”
Section: Discussionmentioning
confidence: 99%
“…Considered a simple, safe and low-cost method, after the advent of portable equipment, it has been of invaluable help in the screening of populations living in endemic areas and in field-based studies of the disease. Taken as a nearly ideal tool in the diagnosis and classification of schistosomiasis, it is now used as a surrogate for the gold-standard in the diagnosis of schistosomiasis-related liver fibrosis (Doehring-Schwerdtfeger et al 1989, Abdel-Wahab et al 1992, Richter et al 1992, Abdel-Wahab & Strickland 1993, pinto-Silva et al 1994, Richter 2000, Kariuki et al 2001, Cota et al 2006, Marinho et al 2006, Ruiz-Guevara et al 2007.…”
mentioning
confidence: 99%
“…Various studies have focused on ultrasound in an effort to reveal abnormalities in the abdominal organs consistent with the diagnosis of chronic schistosomiasis and to identify parameters that relate to quantification of the risk of digestive bleeding (Richter et al 1992, Abdel-Wahab et al 1993, Domingues et al 1993, Eltoum et al 1994, Martins et al 2000. Although some studies show the importance of this diagnostic method, especially regarding evaluation of portal hypertension, its diagnostic precision has not been closely assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Some ultrasound parameters, such as spleen size, diameters of the splenic and portal veins and presence of portosystemic collateral circulation, are related to the quantification of the risk of bleeding from esophageal varices in patients with hepatosplenic schistosomiasis (Richter et al 1992, Abdel-Wahab et al 1993, Domingues et al 1993, Eltoum et al 1994, Richter et al 1998, Martins et al 2000. Prophylactic treatment of portal hypertension is particularly important when the costs and inconveniences of drug treatment and complications from endoscopic and surgical procedures are considered (Martins et al 2000).…”
mentioning
confidence: 99%